The audiobook: the new orality in the digital era - Vallorani, Cecilia María; Gibert, Isabel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The objective of this study is to analyse the audiobook from a pragmatic-communicative point of view and investigate the definitions that different authors have provided about the concept of orality, starting with Zumthor (1985) and Ong (1987) research on the literary theory related to the oral transmission of texts. Likewise, the studies of Bobes (1997) on the dramatic text for the audiobook as a "new dramatic text" leads to the analysis of the application of literary theory in the digital world, seen as a new literary product, evolution from orality to from the written text.